2014
DOI: 10.1007/s11302-014-9410-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine A2B receptor signaling in contribution of cardiac mesenchymal stem-like cells to myocardial scar formation

Abstract: Adenosine levels increase in ischemic hearts and contribute to the modulation of that pathological environment. We previously showed that A 2B adenosine receptors on mouse cardiac Sca1 + CD31− mesenchymal stromal cells upregulate secretion of paracrine factors that may contribute to the improvement in cardiac recovery seen when these cells are transplanted in infarcted hearts. In this study, we tested the hypothesis that A 2B receptor signaling regulates the transition of Sca1 + CD31 − cells, which occurs afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In 1986, Dubey et al (112) first reported that ADO inhibits cardiac fibroblast collagen production via stimulation of A 2 B receptors. Later work further indicated that maneuvers that increase intracellular cAMP diminish collagen production by cardiac fibroblasts (113, 114). This observation led to the demonstration of the homeostatic role of ATP hydrolysis, by the action of ENTPD (CD39) in diminishing collagen production by increasing extracellular ADO levels, which act at A 2 B receptors to raise cAMP and diminish fibroblast production of collagen (115).…”
Section: Modulation Of Peritoneal and Cardiac Fibrosis By Adomentioning
confidence: 99%
“…In 1986, Dubey et al (112) first reported that ADO inhibits cardiac fibroblast collagen production via stimulation of A 2 B receptors. Later work further indicated that maneuvers that increase intracellular cAMP diminish collagen production by cardiac fibroblasts (113, 114). This observation led to the demonstration of the homeostatic role of ATP hydrolysis, by the action of ENTPD (CD39) in diminishing collagen production by increasing extracellular ADO levels, which act at A 2 B receptors to raise cAMP and diminish fibroblast production of collagen (115).…”
Section: Modulation Of Peritoneal and Cardiac Fibrosis By Adomentioning
confidence: 99%
“…, a low-affinity adenosine receptor even expressed by cardiac mesenchymal stem-like cells 46 that arrest cell cycle 46 . In order to highlight the dose-dependent role of adenosine as mediator of ticagrelor effects, we have also performed further experiments by adding exogenous adenosine.…”
mentioning
confidence: 99%
“…In fact, it modulated osteoblast differentiation [227]. Moreover, these receptors also regulate myocardial repair and remodeling by delaying the deactivation of myofibroblasts [228].…”
Section: Selective Full Agonist Antagonist/partial Agonist Allostericmentioning
confidence: 99%